2015
DOI: 10.1098/rsos.150476
|View full text |Cite
|
Sign up to set email alerts
|

A new Early Oligocene toothed ‘baleen’ whale (Mysticeti: Aetiocetidae) from western North America: one of the oldest and the smallest

Abstract: Archaic toothed mysticetes represent the evolutionary transition from raptorial to bulk filter feeding in baleen whales. Aetiocetids, in particular, preserve an intermediate morphological stage in which teeth functioned alongside a precursor of baleen, the hallmark of all modern mysticetes. To date, however, aetiocetids are almost exclusively Late Oligocene and coeval with both other toothed mysticetes and fully fledged filter feeders. By contrast, reports of cetaceans from the Early Oligocene remain rare, lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
77
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(84 citation statements)
references
References 59 publications
5
77
2
Order By: Relevance
“…In contrast, other stem Mysticeti from the mid-late Oligocene (latest Rupelian to Chattian marine stages) are much better known from described material, illustrating vastly different feeding morphologies for geographically and phylogenetically separate groups: The relatively small Mammalodontidae (∼3 m in total length), including Janjucetus hunderi (Fitzgerald, 2006), Mammalodon colliveri (Fitzgerald, 2010), and Mammalodon hakataramea (Fordyce and Marx, 2016) from Australia and New Zealand; the equally small Aetiocetidae (∼2-4 m in length), from the North Pacific Ocean (Emlong, 1966;Marx et al, 2015); and the minke-sized Eomysticetidae (∼6-8 m in length), found in both Northern and Southern hemispheres, represented by several genera (Boessenecker and Fordyce, 2015a,b). Both Mammalodontidae and Aetiocetidae unequivocally possessed functional upper and lower dentitions, while Eomysticetidae either possessed severely reduced or entirely lacked dentition.…”
Section: Paleontological Evidencementioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, other stem Mysticeti from the mid-late Oligocene (latest Rupelian to Chattian marine stages) are much better known from described material, illustrating vastly different feeding morphologies for geographically and phylogenetically separate groups: The relatively small Mammalodontidae (∼3 m in total length), including Janjucetus hunderi (Fitzgerald, 2006), Mammalodon colliveri (Fitzgerald, 2010), and Mammalodon hakataramea (Fordyce and Marx, 2016) from Australia and New Zealand; the equally small Aetiocetidae (∼2-4 m in length), from the North Pacific Ocean (Emlong, 1966;Marx et al, 2015); and the minke-sized Eomysticetidae (∼6-8 m in length), found in both Northern and Southern hemispheres, represented by several genera (Boessenecker and Fordyce, 2015a,b). Both Mammalodontidae and Aetiocetidae unequivocally possessed functional upper and lower dentitions, while Eomysticetidae either possessed severely reduced or entirely lacked dentition.…”
Section: Paleontological Evidencementioning
confidence: 99%
“…Pending studies that more broadly sample these traits across mysticete phylogeny, we argue that patterns of dental evolution and loss in cetaceans should not be a priori linked, neither in step-wise nor correlative models. Lastly, stem Mysticeti show at least four different lineages with markedly disparate feeding morphologies (Mitchell, 1989;Fitzgerald, 2006Fitzgerald, , 2010Boessenecker and Fordyce, 2015a;Marx et al, 2015). The functional and ecological interpretations of these extinct morphologies are unclear and, we argue, potentially over interpreted.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations